2018
DOI: 10.1002/bies.201700229
|View full text |Cite
|
Sign up to set email alerts
|

DNA Repair: The Search for Homology

Abstract: The repair of chromosomal double-strand breaks (DSBs) by homologous recombination is essential to maintain genome integrity. The key step in DSB repair is the RecA/Rad51-mediated process to match sequences at the broken end to homologous donor sequences that can be used as a template to repair the lesion. Here, in reviewing research about DSB repair, I consider the many factors that appear to play important roles in the successful search for homology by several homologous recombination mechanisms. See also the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(108 citation statements)
references
References 113 publications
1
101
0
1
Order By: Relevance
“…Moreover, a recent study has suggested that the underlying causes of these four biomarkers may differ. High TMB and MSI are caused by defects in the DNA damage repair system, which is composed of many proteins in addition to MMR components, including the homologous recombination repair element RecA/Rad51 and the non‐homologous end joining repair element Ku70/Ku80 . Research has shown that in the absence of MSI, mutations in DNA polymerase (POLE) can lead to TMB‐H .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study has suggested that the underlying causes of these four biomarkers may differ. High TMB and MSI are caused by defects in the DNA damage repair system, which is composed of many proteins in addition to MMR components, including the homologous recombination repair element RecA/Rad51 and the non‐homologous end joining repair element Ku70/Ku80 . Research has shown that in the absence of MSI, mutations in DNA polymerase (POLE) can lead to TMB‐H .…”
Section: Discussionmentioning
confidence: 99%
“…30 Shifts, which are not possible by replacing virus segments, may have occurred in coronavirus. Since it does not copy the genome into double-stranded DNA, RNA splicing in nucleus (18) or RNA interference would be used instead of the ordinal homologous recombination by the RecA family (19). Those may also be the cause of frequent indels.…”
Section: Discussionmentioning
confidence: 99%
“…HR is a high-fidelity DNA repair mechanism that functions to rejoin DSBs (37). HR, which occurs in the S or G2 phase of the cell cycle, uses a homologous DNA sequence as a template to guide the faithful repair of DSBs (38).…”
Section: Discussionmentioning
confidence: 99%